Assessing education program learning outcomes - Bahous, Rima (2011)
Teacher education programs help teachers gain knowledge and skills, develop ‘new’ attitudes, and impact their beliefs about teaching, thereby favorably affecting teaching outcomes. In the absence of national standards and formal studies in Lebanon of existing teacher preparation programs, findings of this study could greatly contribute to needed research in the field and inform policy makers. This study examines a pre-service education program at a private university in Lebanon for the purpose of assessing the program’s learning outcomes. Qualitative data were collected from questionnaires, pre and post surveys, and reflective journals focusing on perceptions of an effective teacher before and after training to detect any development from 50 student–teachers enrolled in the senior practicum classes during the scholastic year when the study was conducted. Fifteen student journals were examined for their reflections on principles, facts and techniques acquired, changes in behavior after training, and the relation of learned theory to work field in light of what they had experienced during their 180 h of fieldwork and seminars at the university. Results were then compared to the program’s stated learning outcomes to assess whether they were achieved. Findings indicated that training positively affects student–teachers, but still more rigorous steps should be taken to ensure that all learning outcomes are met. Implications for program training improvement and recommendations for future research are made.